Investigation and analysis of forecasting height of children for talent selection - Wang, F.; Lin, S.; Wang, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This paper suggests an accurate forecasting method for predicting children's future height on the basis of bone age. This study examined male and female juvenile basketball athletes in Shenyang. Based on heredity factors, a comparison between children`s future height and final height was conducted to provide a reliable scientific basis for trainers to identify sports talent. Methods Athlete`s height and date of birth was recorded. Children were recruited for the study. An X optical photograph of arm bone was taken and the time was recorded to evaluate the bone age and forecast height by using the G-P method. The height of the parents was recorded to assist with forecasting the athlete`s future height. Comparison and use of mathematical statistics was used to investigate the athletes' final height. Results There is an 82.6% accuracy rate between the comparison with the bone age forecast and forecasting an athletes' final height. There is a 64.3% accuracy rate by comparison of children's future height according to heredity factors and an athletes' final height. There is a 91.3% accuracy rate by comparing an athlete`s future height and final height by comparing the two methods. Discussion / Conclusions The results indicated the value of using bone age to select children and juvenile sports talent and to forecast athletes' future height in their adolescence; the accuracy rate is 82.6%. There are certain differences in forecasting athletes' height solely by use of bone age or by the use of the heredity factor method. There is a 91.3% accuracy rate by linking the bone age and parents height to forecast children's future height.